Preparation method of large-area tin-based narrow-band-gap perovskite thin film based on solvent engineering
By using a mixed solvent system containing pyridine and vacuum-assisted annealing method in solvent engineering, the problems of uneven crystallization process and void formation of narrow band gap perovskite films are solved, and the preparation of high-quality films and high-efficiency photovoltaic performance are achieved.
Patent Information
- Application Number
- CN202510018879.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
It is difficult to prepare high-quality large-area narrow band gap perovskite films in the prior art, mainly because the divalent tin ions have a large ion radius and weak coordination ability, resulting in uneven crystallization process and low saturation vapor pressure of the coordination solvent, making it easy to form voids.
A mixed solvent system containing pyridine is adopted to form an intermediate phase through the strong coordination effect of pyridine and divalent tin ions, adjust the crystal growth process, and combine it with vacuum-assisted annealing method to quickly extract the solvent to prevent void formation.
A uniform and dense narrow band gap perovskite film preparation was achieved, which significantly improved the film quality and the photovoltaic performance of the corresponding devices, and the photoelectric conversion efficiency reached 22.9%.
Smart Images

Figure CN119836197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for preparing a large-area tin-based narrow-bandgap perovskite film and a device preparation method based on solvent engineering. Background Art
[0002] In the past decade, the photoelectric conversion efficiency of single-junction perovskite solar cells has rapidly increased to more than 26%, gradually approaching the upper limit of the Shockley-Queisser theory. In order to break through the efficiency limitations of single-junction solar cells, researchers have developed and constructed the technology of multi-junction tandem solar cells, which can fully utilize the solar spectrum and reduce thermal losses by stacking absorption layers with different band gaps, thereby further improving the photoelectric conversion efficiency. Among them, with the advantages of low cost, high photoelectric conversion efficiency and continuous production, all-perovskite tandem solar cells are expected to become the first choice for photovoltaics in the future.
[0003] Currently, the efficiency of the most advanced all-perovskite stacked devices has exceeded 30%. However, they are usually prepared by spin coating technology and the device size is small (effective area ~0.1cm 2 ). So far, only a few studies have begun to try to apply high-throughput solution preparation technology (including blade coating, roll-to-roll coating, slot die coating, etc.) to the production of large-area all-perovskite solar modules. However, although this technology has been widely used in the preparation of single-junction perovskite solar modules (~1.5eV), it was found in actual operation that this technology is difficult to directly transfer to the production of all-perovskite stacked solar modules. This is mainly because wide-bandgap and narrow-bandgap perovskite films have their own unique crystallization kinetics, which are difficult to be compatible with the current solvent system. This problem is more serious for tin-based narrow-bandgap perovskites that are easy to crystallize quickly. The internal mechanism is that compared with lead ions (the ionic radius becomes smaller due to lanthanide contraction), divalent tin ions have larger ionic radius and smaller electropositivity, which makes the coordination ability of tin ions with solvents (such as dimethyl sulfoxide and N-methyl-2-pyrrolidone) weaker, and it is difficult to form an effective intermediate phase to fine-tune the crystallization process of perovskites. In addition, these coordinating solvents have low saturated vapor pressures and are easily trapped at the buried perovskite interface during annealing, eventually forming voids. These two challenges severely hinder the preparation of high-quality, large-area narrow-bandgap perovskite films. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention has developed a mixed solvent system containing pyridine for the preparation of narrow bandgap perovskite films. Pyridine and divalent tin ions have a stronger coordination effect, which can effectively form a strong electron donor-acceptor complex intermediate phase, and adjust the crystal growth process by changing the thermodynamic process. In addition, pyridine has a high saturated vapor pressure, and combined with an innovative vacuum-assisted annealing method, the perovskite phase conversion rate is adjusted by changing the kinetic process. Finally, a uniform and dense narrow bandgap perovskite film is obtained, and the corresponding 10.4 cm 2 The all-perovskite tandem solar module achieved a photoelectric conversion efficiency of 22.9%.
[0005] In one aspect, the present invention provides a method for preparing a narrow bandgap perovskite film, comprising:
[0006] S1: Press FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 molar ratio, formamidine iodide (FAI), cesium iodide (CsI), tin iodide (SnI2), lead iodide (PbI2), tin fluoride (SnF2) and lead thiocyanate (Pb(SCN)2) were dissolved in a mixed solvent of DMF (N,N-dimethylformamide) / DMSO (dimethyl sulfoxide) / pyridine, stirred at room temperature for 3 hours, filtered, and obtained a narrow band gap perovskite precursor solution;
[0007] S2: coating the narrow bandgap perovskite precursor solution on the substrate to form a wet film;
[0008] S3: The wet film is vacuum annealed at 100-105°C and 10-100 Pa pressure for 10 min to obtain a narrow bandgap perovskite film.
[0009] In some embodiments, in S1, the volume ratio of DMF:DMSO:pyridine in the mixed solvent is 85%:(15%-5%):(0-10%) and the volume of pyridine is not 0, preferably 85%:5%:10%. In the present invention, a pyridine solvent with high saturated vapor pressure and high coordination ability is selected to replace and reduce the amount of DMSO used in large quantities, which is conducive to the formation of a large amount of intermediate phases, thereby delaying the crystallization rate of narrow bandgap perovskites and reducing the situation where DMSO is easily "captured" by the lower interface. Ultimately, the film quality and the corresponding device efficiency are significantly improved.
[0010] In some embodiments, in S2, the substrate is cleaned before coating, and a transparent ITO (indium tin oxide) conductive glass substrate is selected as the substrate. After being scrubbed with detergent, it is ultrasonically cleaned in deionized water, acetone and isopropanol for 15 minutes respectively; after the ultrasonic cleaning, it is blown dry with nitrogen; finally, it is treated with ultraviolet ozone for about 30 minutes.
[0011] In some embodiments, in S2, a blade coater is used for coating, and the gap between the blade coater and the substrate is set to 60 μm, and the coating speed is 1 mm s -1 , the nitrogen knife pressure is 60psi.
[0012] In a second aspect, the present invention provides a narrow bandgap perovskite film obtained by the above preparation method.
[0013] In a third aspect, the present invention provides a method for preparing a single-junction narrow-bandgap perovskite module, comprising:
[0014] (1) At a substrate temperature of 45°C, at a rate of 5 mm s -1 A conductive poly(3,4-ethylenedioxythiophene)-poly(p-styrenesulfonic acid) (PEDOT:PSS) solution was coated on the cleaned substrate at a speed of 1000 nm, and then annealed in air at 120° C. for 10 min to prepare a hole transport layer;
[0015] (2) coating the narrow bandgap perovskite precursor solution on the substrate treated in step (1), and performing vacuum annealing to obtain a narrow bandgap perovskite film;
[0016] (3) C 60 , BCP and Ag are deposited on the substrate treated in step (2) to obtain a single-junction narrow-bandgap perovskite module.
[0017] In a fourth aspect, the present invention provides a method for preparing an all-perovskite stacked device, comprising:
[0018] Step 1: Press FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 molar ratio, formamidine iodide (FAI), cesium iodide (CsI), tin iodide (SnI2), lead iodide (PbI2), tin fluoride (SnF2) and lead thiocyanate (Pb(SCN)2) were dissolved in a mixed solvent of DMF (N,N-dimethylformamide) / DMSO (dimethyl sulfoxide) / pyridine, stirred at room temperature for 3 hours, filtered, and obtained a narrow band gap perovskite precursor solution;
[0019] Step 2: Press FA 0.7 Cs 0.3 Pb(I 0.6 Br 0.4 )3 in a molar ratio, dissolving FAI, CsI, PbI2 and PbBr2 in a mixed solvent of DMF / DMSO, stirring at room temperature for 3 hours, and filtering to obtain a wide bandgap perovskite precursor solution;
[0020] Step 3: Cleaning of transparent conductive glass substrate;
[0021] Step 4: NiO X (nickel oxide) was coated on a transparent conductive glass substrate by spin coating, transferred to a heating stage at 150°C for annealing for 15 minutes, and after cooling to room temperature, a hole transport layer was obtained;
[0022] Step 5: coating the wide bandgap perovskite precursor solution on the substrate treated in step 4 to form a wet film, and vacuum annealing the wet film at 100-105° C. and 10-100 Pa pressure for 10 minutes to obtain a wide bandgap perovskite film;
[0023] Step 6: Evaporation C 60 After that, the substrate treated in step 5 was transferred to an atomic layer deposition (ALD) system (NCE-200R), and a 15 nm dense SnO2 (tin oxide) film was deposited at 95 °C using tetrakis(dimethylamino)tin(IV) and deionized water as precursors. Then, 1 nm Au (gold) clusters were deposited on the SnO2 layer, and then the Au (gold) clusters were deposited at a substrate temperature of 45 °C at a speed of 5 mm s -1 The PEDOT:PSS solution (diluted with isopropanol, volume ratio of 1:2) was coated on the above layer at a speed of 1:2, and then annealed in air at 100°C for 10 minutes to form a "tunnel junction";
[0024] Step 7: coating the narrow bandgap perovskite precursor solution on the substrate treated in step 6 to form a wet film, and vacuum annealing the wet film at 100-105° C. and 10-100 Pa pressure for 10 minutes to obtain a narrow bandgap perovskite film;
[0025] Step 8: C 60 , BCP and Ag are deposited on the substrate obtained after being processed in step seven to form a full perovskite stacked module device.
[0026] In some embodiments, in step 1, the volume ratio of DMF:DMSO:pyridine in the mixed solvent is 85%:(15%-5%):(0-10%) and the volume of pyridine is not 0, preferably 85%:5%:10%.
[0027] In some embodiments, in step 2, the volume ratio of DMF / DMSO in the mixed solvent is 60%:40%.
[0028] In some embodiments, in step three, a transparent ITO conductive glass substrate is selected as the substrate, scrubbed with detergent, and then ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes respectively; after the ultrasonic cleaning, it is blown dry with nitrogen; finally, the transparent conductive glass substrate is treated with ultraviolet ozone for about 30 minutes.
[0029] In a fifth aspect, the present invention provides an all-perovskite stacked device obtained by the above-mentioned preparation method.
[0030] In some embodiments, the photoelectric conversion efficiency of the all-perovskite stack device is 22.9%.
[0031] Technical Effects
[0032] The present invention suppresses the crystallization rate of narrow-bandgap perovskite by solvent engineering based on high coordination. Thanks to its strong electron pair donor ability, pyridine can effectively coordinate with divalent tin ions to form an intermediate phase, thereby suppressing the rapid heterogeneous nucleation during the crystallization process. The crystal quality and optoelectronic properties of narrow-bandgap perovskite films prepared based on coordination solvents were studied using X-ray diffraction (XRD), scanning Kelvin probe force microscopy (KPFM) and conductive atomic force microscopy (C-AFM). It can be seen that the addition of pyridine can effectively improve the crystallization quality of narrow-bandgap perovskite films while reducing the defect density.
[0033] The present invention selects a coordination solvent with high saturated vapor pressure and constructs a vacuum-assisted annealing process to quickly extract the solvent. Combining the high saturated vapor pressure of pyridine with the vacuum-assisted annealing process can effectively accelerate the extraction rate of the solvent. This prevents the problem of solvent residues at the bottom interface and the appearance of voids. By comparing the scanning electron microscopy (SEM) images of narrow bandgap perovskite films prepared based on different solvent systems, it can be seen that the voids in the bottom film disappear after adding pyridine.
[0034] The present invention improves the quality of perovskite film and the photovoltaic performance of the corresponding device as a whole. The photoelectric conversion efficiency of narrow-bandgap perovskite cells and modules is significantly improved. Finally, the present invention obtains an all-perovskite solar photovoltaic module (10.4 cm2) with an efficiency of 22.9%. 2 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The overall route to improve the quality of narrow-bandgap perovskite films through coordination solvent engineering is shown;
[0036] Figure 2 is a schematic diagram of the vacuum assisted annealing process;
[0037] Figure 3 The state of SnI2 powder in different solvent systems is shown;
[0038] Figure 4 The photographs of narrow bandgap perovskite precursor solutions after N2-assisted blade coating process in different solvent systems are shown;
[0039] Figure 5shows that pyridine and Sn 2+ Fourier transform infrared spectra of interactions between ions;
[0040] Figure 6 XRD patterns of narrow bandgap perovskite films obtained by different preparation methods;
[0041] Figure 7 The cross-sectional SEM images of narrow bandgap perovskites prepared in different solvent systems;
[0042] Figure 8 The optoelectronic properties of narrow-bandgap perovskite films prepared based on different solvent systems are shown;
[0043] Fig. 9 A photo of a large-area narrow-bandgap perovskite film prepared by the N2-assisted blade coating process;
[0044] Fig.10 The current-voltage (JV) curves of narrow bandgap perovskite solar cells prepared based on different proportions of pyridine;
[0045] Fig.11 The following are actual photos of narrow bandgap modules, and photovoltaic performance diagrams of single-junction narrow bandgap and stacked modules. DETAILED DESCRIPTION
[0046] The following describes the preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0047] Example 1: Preparation of single-junction narrow-bandgap perovskite module
[0048] (1) Narrow bandgap perovskite (FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3) Preparation of precursor solution
[0049] 289.0 mg of FAI, 109.2 mg of CsI, 391.1 mg of SnI2, 484.0 mg of PbI2, 16.0 mg of SnF2 and 5.2 mg of Pb(SCN)2 were dissolved in 1 mL of a mixed solvent of DMF / DMSO / pyridine (volume ratio 85%:5%:10%) to obtain a narrow bandgap perovskite (FAI). 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3) Precursor solution.
[0050] (2) Cleaning of transparent conductive glass substrate
[0051] The etched transparent ITO conductive glass substrate was scrubbed with detergent and transferred to a cleaning fence. It was ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes respectively. After the ultrasonic cleaning, it was blown dry with nitrogen for later use. Finally, it was treated with ultraviolet ozone for about 30 minutes as a substrate.
[0052] (3) Preparation of hole transport layer
[0053] At a coater temperature of 45°C, the coating speed was 5 mm s -1 A PEDOT:PSS solution (diluted with isopropanol in a volume ratio of 1:2) was coated on the cleaned substrate at a speed of 1:2, and then annealed in air at 120° C. for 10 minutes to form a hole transport layer.
[0054] (4) Blade coating of narrow bandgap perovskite films
[0055] Set the gap between the blade coater and the substrate treated in step (3) to 60 μm, and the coating speed to 1 mm s -1 , the nitrogen knife pressure is 60psi, and the narrow bandgap perovskite precursor solution is coated on the substrate to form a wet film. Subsequently, vacuum annealing is performed at 100°C and 10-100Pa pressure for 10 minutes to obtain a narrow bandgap perovskite film. This implementation step can also be applied to slot die coating, spraying or evaporation of perovskite. Here, in order to solve the problem that traditional annealing methods are difficult to effectively extract solvents with low saturated vapor pressure, the present invention innovatively adopts a vacuum-assisted annealing method, that is, annealing operation is performed on a hot stage at 105°C under a vacuum degree of 10-100Pa, such as Figure 2 As shown in Figure 2, it can reduce the vacuum degree to 10-100 Pa in a short time (<3s). This allows solvents such as DMF / DMSO to be quickly extracted from the wet film, reducing the holes in the interface under the perovskite and further improving the film quality.
[0056] (5) Preparation of single-junction narrow-bandgap perovskite modules
[0057] By thermal evaporation technology, 20nm C 60 , 5 nm of BCP and 120 nm of Ag are deposited on the substrate treated in step (4) to form a single-junction narrow-bandgap perovskite module.
[0058] Figure 1 The overall route of improving the quality of narrow-bandgap perovskite films through coordination solvent engineering is shown. The present invention selects pyridine solvents with high saturated vapor pressure and high coordination ability to replace and reduce the amount of DMSO used, which is conducive to the formation of a large number of intermediate phases, thereby slowing down the crystallization rate of narrow-bandgap perovskites and reducing the situation where DMSO is easily "captured" by the lower interface. Ultimately, the film quality and the corresponding device efficiency are significantly improved.
[0059] This application compares and analyzes different D N (electron pair donating ability) value of the solvent's coordination ability. Figure 3 As shown, 1.0 mol / L SnI2 powder was added to DMSO and pyridine respectively. SnI2 was simply dissolved in DMSO (such as Figure 3 a). However, in pyridine (such as Figure 3 b), due to the strong coordination ability between them, a yellow SnI2·pyridine complex is formed.
[0060] Comparative Example 1: Preparation of single-junction narrow-bandgap perovskite module
[0061] A single-junction narrow-bandgap perovskite module was prepared by the same method as in Example 1, except that in step (1), DMSO / DMF solvent (volume ratio 15%:85%) was used as the solvent for the narrow-bandgap perovskite precursor solution.
[0062] Figure 4 Figure 1 shows photos of narrow bandgap perovskite precursor solutions after N2-assisted blade coating process in different solvent systems. It can be seen that in Comparative Example 1, the precursor based on DMSO / DMF solvent quickly crystallized and directly converted into a black perovskite phase (such as Figure 4 This is mainly due to the interaction between DMSO and Sn 2+ The weak coordination between ions results in insufficient formation of intermediate phases. Figure 4 b (Example 1), the high D N After adding high value of pyridine into the solvent system, a uniform brown film was formed after the N2-assisted blade coating process, corresponding to the pyridine-induced mesophase.
[0063] The present invention uses Fourier transform infrared (FTIR) to confirm that pyridine and Sn 2+ Strong electron donor-acceptor interactions between ions ( Figure 5 ).like Figure 5 As shown, 1042cm -1 The absorption peak at 1068 cm is attributed to the stretching vibration of S=O (ν(S=O)) in DMSO. No obvious shift of this absorption peak was found in the FTIR spectrum of DMSO·SnI2. In contrast, in the spectrum of SnI2·pyridine, the absorption peak related to the stretching vibration of CN (ν(CN)) in pyridine shifted from 1068 cm -1 Displacement to 1064cm -1 In addition, at 1003cm -1 and 1006cm -1 A new signal was detected at 2+These findings confirm that pyridine and Sn are more stable than DMSO. 2+ ions exhibit stronger electron donor-acceptor interactions.
[0064] The XRD patterns of narrow bandgap perovskite films prepared by different methods (DMF / DMSO as solvent, DMF / pyridine / DMSO as solvent, DMF / pyridine / DMSO as solvent and vacuum assisted annealing) are shown in Figure 2. Figure 6 As shown in the figure, it can be seen that compared with the perovskite film prepared based on DMSO solvent, after adding pyridine, the intensity of all characteristic XRD diffraction peaks of narrow bandgap perovskite is enhanced, indicating the improvement of the crystallization quality of narrow bandgap perovskite. After vacuum assisted annealing (VA), the crystallization quality of narrow bandgap perovskite is further improved.
[0065] Figure 7 The cross-sectional SEM images of narrow bandgap perovskites prepared in different solvent systems. The samples were prepared under vacuum assisted annealing by default. Figure 7 As shown in a, some voids are still observed at the bottom of the perovskite film prepared based on DMSO solvent. This is because the DMSO molecules are trapped at the bottom interface of the perovskite and are difficult to escape, which eventually leads to film damage. Figure 7 b), a dense, uniform, and highly columnar narrow-bandgap perovskite crystal was obtained.
[0066] The present invention uses scanning Kelvin probe force microscopy and conductive atomic force microscopy to study the optoelectronic properties of narrow bandgap perovskite films prepared based on different solvent systems ( Figure 8 ).like Figure 8 As shown in Figs. a and 8b, the narrow bandgap perovskite film prepared based on DMSO solvent has a wide contact surface potential distribution of 40 mV and a wide leakage current distribution of ~4.2 pA, with a high leakage current of ~12.0 pA. This highly uneven distribution of surface charge and leakage current is mainly attributed to the high density of active defects in the perovskite film. In contrast, Figure 8 c and 8d, after adding pyridine, the wide contact surface potential distribution, wide leakage current distribution and leakage current of the perovskite film are significantly reduced to about ~20mV, ~3.5pA and ~7.2pA, respectively. This shows that the addition of pyridine can significantly improve the quality of narrow bandgap perovskite films and greatly reduce the density of defects.
[0067] Fig. 9 The large-area narrow-bandgap perovskite film prepared by the N2-assisted blade coating process is shown, indicating that the process of the present invention can prepare high-quality large-area narrow-bandgap perovskite films.
[0068] Example 2
[0069] A single-junction narrow-bandgap perovskite module was prepared by the same method as in Example 1, except that in step (1), different proportions of pyridine (based on a 100 vol% mixed solvent, DMF accounts for 85 vol%, pyridine accounts for 0-10 vol%, and DMSO accounts for 15%-5%) were used as the solvent for the narrow-bandgap perovskite precursor solution.
[0070] The current-voltage (JV) curve of the prepared single-junction narrow-bandgap perovskite module is shown in Fig.10 shown.
[0071] For the reference narrow-bandgap perovskite solar cell (with 0 pyridine volume), the photoelectric conversion efficiency (PCE) is 18.5%, the open circuit voltage (VOC) is 0.814 V, and the short circuit current (JSC) is 30.2 mA cm -2 , the fill factor (FF) is 75.2%. In the mixed solvent system, as the ratio of pyridine increases from 0 to 10 vol%, all photovoltaic parameters including PCE, VOC, JSC and FF are significantly enhanced.
[0072] The best PCE, VOC, JSC, and FF were obtained after adding 10 vol% pyridine into the DMSO-DMF solvent system, with a PEC of 22.0%, a VOC of 0.853 V, and a JSC of 32.5 mA cm -2 , FF is 79.2%.
[0073] However, the excessive presence of pyridine, which further increases to 13 vol% and 15 vol% in the mixed solvent, leads to poor photovoltaic performance of narrow-bandgap perovskite solar cells.
[0074] Example 3: Preparation of all-perovskite stacked module
[0075] Step 1: Narrow Bandgap Perovskite (FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3) Preparation of precursor solution
[0076] 289.0 mg of FAI, 109.2 mg of CsI, 391.1 mg of SnI2, 484.0 mg of PbI2, 16.0 mg of SnF2 and 5.2 mg of Pb(SCN)2 were dissolved in 1 mL of a mixed solvent of DMF / DMSO / pyridine (volume ratio 85%:5%:10%) to obtain a narrow bandgap perovskite (FAI). 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3) Precursor solution.
[0077] Step 2: Wide Bandgap Perovskite (FA0.7 Cs 0.3 Pb(I 0.6 Br 0.4 )3) Preparation of precursor solution
[0078] 192.6 mg of FAI, 124.8 mg of CsI, 295.0 mg of PbI2 and 352.3 mg of PbBr2 were dissolved in 1 mL of a DMF / DMSO mixed solvent (60%:40% by volume) to obtain a wide bandgap perovskite (FA 0.7 Cs 0.3 Pb(I 0.6 Br 0.4 )3) precursor solution;
[0079] All perovskite precursor solutions were stirred at room temperature for 3 h and filtered through a 0.22 μm polytetrafluoroethylene (PTFE) membrane before use.
[0080] Step 3: Cleaning of transparent conductive glass substrate
[0081] The etched transparent ITO (indium tin oxide) conductive glass substrate was scrubbed with detergent and transferred to a cleaning fence. It was ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes respectively. After the ultrasonic cleaning, it was blown dry with N2 for standby use. Finally, it was treated with ultraviolet ozone for about 30 minutes as a substrate.
[0082] Step 4: Preparation of hole transport materials
[0083] 10 mg / mL NiO X (Nickel oxide) was coated on the substrate by spin coating at a speed of 4000 rpm for 30 seconds. It was then transferred to a heating table at 150°C for annealing for 15 minutes to form a hole transport layer. It was used after cooling to room temperature.
[0084] Step 5: Blade coating of wide bandgap perovskite film
[0085] Set the gap between the blade coater and the substrate treated in step 4 to 30 μm and the coating speed to 3 mm s -1 , N2 knife pressure is 60psi, the wide bandgap perovskite precursor solution is coated on the substrate to form a wet film. Subsequently, vacuum annealing is performed at 100°C and 10-100Pa pressure for 10 minutes to form a wide bandgap perovskite film. This implementation step can also be applied to slot die coating, spray coating or evaporation of perovskite.
[0086] Step 6: Preparation of tunnel junction
[0087] After evaporating 20nm of C 60After that, the substrate treated in step 5 was transferred to the ALD system, and a 15nm dense SnO2 film was deposited at 95°C using tetrakis(dimethylamino)tin(IV) and deionized water as precursors. Then, 1nm Au (gold) clusters were deposited on the SnO2 layer, and then the coating was continued at a temperature of 45°C at a speed of 5mm s -1 A PEDOT:PSS solution (diluted with isopropanol in a volume ratio of 1:2) was coated on the above layer at a speed of 100°C and then annealed in air at 100°C for 10 min to form a “tunnel junction”.
[0088] Step 7: Blade coating of narrow bandgap perovskite film
[0089] Set the gap between the blade coater and the substrate treated in step 6 to 60 μm and the coating speed to 1 mm s -1 , N2 knife pressure is 60psi, and the narrow bandgap perovskite precursor solution is coated on the substrate to form a wet film. Subsequently, vacuum annealing is performed at 100°C and 10-100Pa pressure for 10 minutes to form a narrow bandgap perovskite film. This implementation step can be applied to slot die coating, spray coating or evaporation of perovskite.
[0090] Step 8: Preparation of stacked module devices
[0091] By thermal evaporation technology, 20nm C 60 , 5 nm of BCP and 120 nm of Ag are deposited on the substrate obtained after being processed in step seven.
[0092] Etching of all-perovskite tandem photovoltaic micromodules
[0093] The transparent ITO conductive glass substrate, hole transport layer / wide bandgap perovskite film / tunnel junction / narrow bandgap perovskite film / electron transport layer and Ag (silver) electrode were etched by laser scriber (GT-LS150-G) to form P1, P2 and P3 patterns. The widths of sub-cells, P1, P2 and P3 are 6.7mm, 30μm, 120μm and 100μm respectively. The effective area of the module is 10.4cm 2 .
[0094] The actual photos of narrow bandgap modules, the photovoltaic performance diagrams of single junction narrow bandgap and stacked modules are shown in the figure. Fig.11 As shown. Fig.11 As shown in a, the mini module consists of 4 sub-units, and the width of each sub-unit and the dead zone are designed to be 6.7 and 0.35 mm respectively, so the corresponding geometric coefficient is 94.7%. The upper cover mask is used for component testing, and its effective area is 10.4 cm 2The narrow-bandgap perovskite mini-module achieves a PCE of 16.3%, a VOC of 3.25 V, an ISC of 72.6 mA, and a FF of 71.7% under reverse sweep, and shows negligible hysteresis ( Fig.11 b).
[0095] The prepared all-perovskite tandem mini-module has a high PCE of 22.9%, a VOC of 8.10 V, an ISC of 37.0 mA, and a FF of 79.5% under reverse scanning. Fig.11 c and Table 1).
[0096] Table 1: Photovoltaic performance of single junction narrow bandgap, wide bandgap modules and corresponding stacked modules
[0097] Battery Type Open circuit voltage[V] Short circuit current [mA] Fill factor [%] efficiency[%] Narrow Bandgap Modules 3.25 72.6 71.7 16.3 Wide Bandgap Modules 5.13 40.6 79.2 15.9 Laminated Module 8.10 37.0 79.5 22.9
[0098] (Note: The device structure of the narrow (wide) bandgap module is: ITO electrode layer / hole transport layer / narrow (wide) bandgap perovskite film / electron transport layer / Ag electrode; the device structure of the stacked module is: ITO electrode layer / hole transport layer / wide bandgap perovskite film / tunneling junction / narrow bandgap perovskite film / electron transport layer / Ag electrode)
[0099] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a narrow bandgap perovskite film, comprising: S1: Press FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 molar ratio, dissolving formamidine iodide, cesium iodide, tin iodide, lead iodide, tin fluoride and lead thiocyanate in a mixed solvent of N,N-dimethylformamide (DMF) / dimethyl sulfoxide (DMSO) / pyridine, stirring at room temperature for 3 hours, filtering, and obtaining a narrow band gap perovskite precursor solution; S2: coating the narrow bandgap perovskite precursor solution on the substrate to form a wet film; S3: The wet film is vacuum annealed at 100-105°C and 10-100 Pa pressure for 10 min to obtain a narrow bandgap perovskite film.
2. The preparation method according to claim 1, wherein In S1, the volume ratio of DMF:DMSO:pyridine in the mixed solvent is 85%:(15%-5%):(0-10%) and the volume of pyridine is not 0.
3. The preparation method according to claim 1, wherein In S2, the substrate is cleaned before coating, and a transparent ITO conductive glass substrate is selected as the substrate. After being scrubbed with detergent, it is ultrasonically cleaned in deionized water, acetone and isopropanol for 15 minutes respectively; after the ultrasonic cleaning, it is blown dry with nitrogen; finally, it is treated with ultraviolet ozone for about 30 minutes.
4. The preparation method according to claim 1, wherein In S2, a blade coater was used for coating, the gap between the blade coater and the substrate was set to 60 μm, and the coating speed was set to 1 mm s -1 , the nitrogen knife pressure is 60psi.
5. A narrow bandgap perovskite film obtained by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a single-junction narrow-bandgap perovskite module, comprising: (1) At a coater temperature of 45°C, at a rate of 5 mm s -1 A conductive poly(3,4-ethylenedioxythiophene)-poly(p-styrenesulfonic acid) solution (PEDOT:PSS) was coated on the cleaned substrate at a speed of 1000 nm, and then annealed in air at 120° C. for 10 min to prepare a hole transport layer; (2) coating the narrow bandgap perovskite precursor solution according to claim 1 on the substrate treated in step (1), and performing vacuum annealing to obtain a narrow bandgap perovskite film; (3) Fullerene (C 60 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) and silver (Ag) are deposited on the substrate treated in step (2) to obtain a single-junction narrow-bandgap perovskite module.
7. A method for preparing an all-perovskite stacked device, comprising: Step 1: Press FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 molar ratio, dissolving formamidine iodide, cesium iodide, tin iodide, lead iodide, tin fluoride and lead thiocyanate in a mixed solvent of DMF / DMSO / pyridine, stirring at room temperature for 3 hours, filtering, and obtaining a narrow band gap perovskite precursor solution; Step 2: Press FA 0.7 Cs 0.3 Pb(I 0.6 Br 0.4 )3 in a molar ratio, dissolving FAI, CsI, PbI2 and PbBr2 in a mixed solvent of DMF / DMSO, stirring at room temperature for 3 hours, and filtering to obtain a wide bandgap perovskite precursor solution; Step 3: Cleaning of transparent conductive glass substrate; Step 4: Spin-coat nickel oxide on the cleaned transparent conductive glass substrate in step 3, transfer to a heating platform at 150° C. for annealing for 15 minutes, and cool to room temperature to obtain a hole transport layer; Step 5: coating the wide bandgap perovskite precursor solution on the substrate treated in step 4 to form a wet film, and vacuum annealing the wet film at 100-105° C. and 10-100 Pa pressure for 10 minutes to obtain a wide bandgap perovskite film; Step 6: After evaporating C60, the substrate treated in step 5 was transferred to the ALD system (NCE-200R), and a 15nm dense SnO2 film was deposited at 95°C using tetrakis(dimethylamino)tin(IV) and deionized water as precursors. Then, 1nm Au clusters were deposited on the SnO2 layer, and then the coating machine temperature was 45°C at a speed of 5mm s -1 The PEDOT:PSS solution was coated on the treated substrate at a speed of 100°C and then annealed in air at 100°C for 10 minutes to form a "tunnel junction". Step 7: coating the narrow bandgap perovskite precursor solution on the substrate treated in step 6 to form a wet film, and vacuum annealing the wet film at 100-105° C. and 10-100 Pa pressure for 10 minutes to obtain a narrow bandgap perovskite film; Step 8: Deposit C60, BCP and Ag on the substrate processed in step 7 by thermal evaporation technology to form a full perovskite stacked module device.
8. The preparation method according to claim 7, wherein In step six, the PEDOT:PSS solution is diluted with isopropanol at a volume ratio of 1:
2.
9. The preparation method according to claim 7, wherein: In step 1, the volume ratio of DMF:DMSO:pyridine in the mixed solvent is 85%:(15%-5%):(0-10%) and the volume of pyridine is not 0.
10. An all-perovskite stacked device obtained by the preparation method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Method for preparing perovskite thin film based on additive engineering and photoelectric application thereof
CN112582544A
Preparation method of 4-pyridine methylamine bromide optimized tin-lead mixed perovskite solar cell
CN113437226A
Preparation method of large-area wide-band-gap perovskite top cell for laminated cell
CN116782730A
Tin-containing perovskite solar cell doped with 3-trifluoromethylpyridine and preparation method thereof
CN118973277A
Processing of perovskite films using inks with complexing agents
US20200287137A1